Validation Instruments for Local Culture-Based Learning Media - Laksana, Dek Ngurah Laba (Universitas Pendidikan Ganesha, 2024)
A tool for evaluating the media's quality is necessary for it to be an effective learning medium. Thus, the creation of educational media is essential, particularly those that are rooted in the local way of life. The aim of this research is to generate validation instruments for learning media products based on design and media aspects, particularly for culturally based learning media, that exhibit both validity and reliability. The 3D research and development model (define, design, develop) is used in this study. Three specialists who act as instrument validators make up the data sources. A questionnaire in the form of an assessment sheet for media and instructional design tools is used as part of the data gathering method. Tests for reliability and validity are two types of data analysis approaches. A descriptive analysis is then performed on the gathered data. The research yielded 15 statements that will serve as expert design evaluation instruments and 10 statements that will serve as expert instructional media assessment instruments. Expert assessments show that the assessment tools for instructional media and design are applicable for application. Furthermore, both instruments have strong empirical validity. It is anticipated that the findings of this study will advance knowledge, particularly in the area of developing tools for evaluating specialists in media and instructional design.